Electric Quadrupole Transitions of Some Even-Even Neon Isotopes - Radhi, R. A.; Flaiyh, G. N.; Raheem, E. M. (Iraqi Journal of Science, 2023)
The reduced electric quadrupole transition strengths B(E2) from the first excited2+ state to the ground 0+ state of some even-even Neon isotopes (18,20,22,24,26,28Ne)have been calculated. All studied isotopes composed of 16O nucleus that isconsidered as an inert core and the other valence particles considered to move overthe sd-shell model space within 1d5/2, 2s1/2 and 1d3/2 orbits.The configuration mixing shell model with limiting number of orbitals in themodel space outside the inert core fail to reproduce the measured electric transitionstrengths. Therefore, and for the purpose of enhancing the calculations, thediscarded space has been included through a microscopic theory which considers aparticle-hole excitations from the core orbits and from the model space orbits intothe higher orbits with 2 excitations. These effects are called core-polarizationeffects.The transition strengths have been calculated with effective nucleon chargesdeduced from the core polarization calculations, and calculated with standardeffective nucleon charges eeff ep  1.3 for the proton and e e effn  0.5 for neutron.The calculations are based on sd-shell model space with USDB interactions.The harmonic oscillator potential is used to generate the single particle matrixelements, where the value of the size parameter b is adjusted to get the experimentalroot mean square matter radii for each isotope.